PENGARUH SERVICE QUALITY DAN PRICE PERCEPTION TERHADAP LOYALITAS YANG DIMEDIASI OLEH KEPUASAN PELANGGAN - Irfan Saputra Iskandar; Saparso Saparso; Soegeng Wahyoedi (Referensi : Jurnal Ilmu Manajemen dan Akuntansi, 2020)
This study aims to determine how customer ratings of service quality, price perceptions, satisfaction and customer loyalty and evaluate the influence of service quality, and price perception variables, on customer loyalty influenced customer satisfaction. This study took 100 respondents by means of nonprobability convenience sampling. Data obtained through questionnaires, the process of collecting data in this study using online media platforms. The technique used in this study is PLS-SEM by using the SmartPLS 3.2.8 program that is used to identify the relationship of the influence of Service Quality and Price Perception variables on Loyalty and Customer Satisfaction as intervening variables. The effect of Service Quality on First Media subcriber satisfaction was 0.451 with p-value 0.000 0.05. The effect of Price Perception on First Media subcriber satisfaction was 0.54 with a p-value of 0,000 0.05. While the effect of Service Quality on Subcriber Loyalty is 0.221 with p-value 0.004 0.05. The effect of Price Perception on Subcriber Loyalty is 0.181 with a p-value of 0.025 0.05